PHILOSOPHICAL FOUNDATION OF RELIGIOUS COURT COMPETENCE TOWARDS ENCUMBRANCE RIGHT EXECUTION - Abd. Shomad; Rahadi Wasi Bintoro (Faculty of Law, Universitas Jenderal Soedirman, 2018)
Religious court as forefront in economic sharia dispute resolution in litigation has not ideal place to perform their duty since there are still regulation conflicts such as implementation of encumbrance right execution which still becomes a domain in district court. As explained, this article discusses phi-losophical foundation of Religious Court competence to resolve economic sharia issues. In regard to this, conceptual approach, law approach and historical approach are respectively used. Based on the analysis, basic competence of religious court is Islamic personality principle which carries the use of Islamic law elements (sharia principle) in its legal relationship. From the analysis the implication is drawn that as long as a dispute belongs to economic sharia, then it is Religious Court which is com-petent to handle including court decision.Keywords: law enforcement, economic sharia dispute, absolute competence, court decision implementation